Common in atherogenesis and carcinogenesis: clonal hematopoiesis - A. A. Sleptsov; M. S. Nazarenko; V. Р. Puzyrev (Российский кардиологический журнал, 2023)
Clonal hematopoiesis is a common age-dependent state accompanied by the expansion of mutant hematopoietic stem cells as a result of somatic mutations and is associated with a high risk of hematopoietic neoplasms and cardiovascular diseases. Clonal hematopoiesis in human ontogenesis occurs asymptomatically, and the fraction of mutant clones can exceed more than 2% of the total pool of circulating nucleated blood cells by age 70. Due to the variability of the accumulation rate of mutant clones, signs of clonal hematopoiesis can be observed at a younger age. Clonal hematopoiesis may act as a benign, precancerous condition and a strong factor for acute cardiovascular events such as myocardial infarction and stroke. Current evidence indicates that somatic mutations in driver genes of clonal hematopoiesis significantly increase the risk of acute conditions such as acute myeloid leukemia and acute myocardial infarction. The high mortality and morbidity of cardiovascular and cancer diseases, and their strong association with clonal hematopoiesis, make it of indeterminate potential worthy of close attention.